An integrated view of biofilm formation in Rhizobia - Rinaudi, Luciana Veronica (2010)
Biofilms are bacterial communities enclosed within an extracellular matrix of polysaccharides produced by the bacteria, which adhere to a living or an inert macrosurface. In nature, biofilms constitute a protected growth modality allowing bacteria to survive in hostile environments. Studies of environmental isolates have revealed a highly ordered, three-dimensional organization of the extracellular matrix, which has important implications for biofilm physiology. The zone of soil immediately surrounding a plant root where complex biological and ecological processes occur, termed rhizosphere, forms an environment that fulfills the requirements for biofilm formation, including sufficient moisture and supply of nutrients, which are provided by the plant. Biofilm formation on plants appears to be associated with symbiotic and pathogenic responses, but it is unclear how plants regulate the association. Biofilms function as structures resistant against stress factors such as desiccation, UV radiation, predation, and antibiosis, which help create protective niches for rhizobia. However, the role of biofilms in rhizobial–legume symbiosis remains to be clarified. Here, the mechanisms involved in bacterial biofilm formation and attachment on plant roots, and the relation of these mechanisms to rhizobial function and survival are reviewed.